The Level of Awareness of Kindergarten Teachers at Baghdad Al-Karkh Second Education Directorate of the Importance of Digital Education - Alwan, Ola Hussein (Journal of Educational and Psychological Sciences, 2025)
The current research aimed to identify the The Level of Awareness of Kindergarten Teachers at Baghdad Al-Karkh Second Education Directorate of the Importance of Digital Education. To achieve the research objective, the researcher adopted a descriptive analytical approach, and a research tool (the questionnaire) was developed. The research sample consisted of (187) teachers selected randomly from kindergartens affiliated with the Baghdad Al-Karkh Second Education Directorate for the academic year 2024/2025. After conducting statistical analyses, the researcher found that kindergarten teachers have an awareness of the importance of digital education, with a general arithmetic mean of the sample being (2.29). Accordingly, conclusions, recommendations, and suggestions were reached.